Evaluasi Efektivitas Kurikulum Pendidikan Vokasional Agribisnis dalam Meningkatkan Keterampilan Praktis Petani - Bambang Irawan; Vina Oktariana; Tika Dewi; Zainal Arifin; Ade Rahmad Kurniawan (CV. Creative Tugu Pena, 2021)
This study aims to evaluate the effectiveness of the vocational agribusiness education curriculum in enhancing participants’ practical skills, particularly farmers. The research is based on the gap between curriculum content and real field needs, such as the mastery of appropriate agricultural technology, sustainable farm management, and digital marketing. A qualitative approach was employed using the CIPP evaluation model (Context, Input, Process, Product). Data were collected through in-depth interviews, observation, and documentation of the vocational agribusiness training program implementation at ITS NU Lampung. The findings show that although the curriculum is conceptually relevant, there are shortcomings in its implementation, especially in adapting the material to local needs and the limitations of training facilities. Therefore, the curriculum needs to be reviewed and refined regularly to become more adaptive, contextual, and applicable. Continuous evaluation based on participant feedback is essential to improving the quality of vocational education in the agribusiness sector.